A Blog to Teach English in High School during the Covid-19 Confinement - Cruz Sánchez, María de los Ángeles; Vez López, Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This research explored the outcomes of using a blog to upload the content of EFL classes during the Covid-19 confinement) to discover to what extent the adaptation of this e-tool could be of benefit to access content for economically disadvantaged students. This study was carried out in a high school located in Veracruz, México. The participants were 171 second semester students who were taking the subject Inglés II from February 2021 to July 2021; during that period students accessed the content of the EFL course using a blog. The data were collected through questionnaires and interviews to obtain a close perception of emergency remote teaching in this particular scenario. The main findings indicated predominantly positive experiences related to accessibility to the asynchronous course in the blog, as well as perceived improvement in writing and reading skills in a large scale, whereas listening and speaking skills improved in a minor scale